Advances and Potentials of NiOx Surface Treatments for p−i−n Perovskite Solar Cells. Issue 3 (8th March 2022) - Tiwari, Nidhi; Arianita Dewi, Herlina; Erdenebileg, Enkhtur; Narayan Chauhan, Ram; Mathews, Nripan; Mhaisalkar, Subodh; Bruno, Annalisa
Abstract : Modified NiOx Films In article number 2100700, Annalisa Bruno and co‐workers discussed a variety of surface modifications and their impacts on the structural and optoelectronic properties of the NiOx. The main alteration strategies are based on physical (UV‐ozone, oxygen, argon, and/or helium plasma), chemical (interlayer passivation), and doping treatments. The effects of modified NiOx films on the power conversion efficiency and stability of p‐i‐n perovskite solar cells have been analyzed. Finally, the current challenges and future outlooks have also been discussed.